Current Challenges and Advances in Organ Donation and Transplantation - Tsoulfas, Georgios (IntechOpen, 2023)
Organ donation and transplantation is a highly specialized and challenging field of medicine that has witnessed tremendous advancements during the last few decades. This book provides a comprehensive overview of the challenges involved in organ donation and transplantation, including ethical, legal, and medical issues, as well as the technical and immunological problems facing experts involved in the care of transplant patients. Over three sections, chapters address such topics as the different types of donations and transplants, technical and surgical aspects of transplantation, and ways to achieve transplant tolerance.